Pozzolanic improvements to fly ash when removing unburned carbon - Roldán Latorre, Walter; Garcés Arroyo, Jorge (Revista de la Construcción. Journal of Construction, 2018)
Through a very simple washing process with water, the unburned carbon is separated and removed from the fly ash. In this work, mixtures of mortar with 30% Portland cement replacement are made by different additions: integral fly ash (obtained from thermoelectric), washed fly ash (removing unburned carbon by washing), unburned carbon and limestone filler (limestone rock dust). To determine better the pozzolanic contribution of the additions, 5% gypsum (with respect to the weight of the binder) is added to the mixtures not hardened. With these mixtures, specimens are made for tests to rupture at 7, 28 and 90 days of age, kept submerged in water and also special specimens kept in similar condition measuring length variations. It is detected that the substitution of portland cement by unburned carbon, significantly reduces the mechanical resistance at any age and does not contribute to protection against sulphate attacks. It is concluded that the unburned carbon does not possess pozzolanic properties and its withdrawal generates benefits to the fly ash in the search to improve the pozzolanic performance in concrete mixtures.